2013
DOI: 10.5194/acp-13-10787-2013
|View full text |Cite
|
Sign up to set email alerts
|

Ozone seasonality above the tropical tropopause: reconciling the Eulerian and Lagrangian perspectives of transport processes

Abstract: Abstract. We aim to reconcile the recently published, apparently contrasting results regarding the relative importance of tropical upwelling versus horizontal transport for the seasonality of ozone above the tropical tropopause. Different analysis methods in the literature (Lagrangian versus Eulerian, and isentropic versus pressure vertical coordinates) yield different perspectives of ozone transport, and the results must be carefully compared in equivalent terms to avoid misinterpretation. By examining the La… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 12 publications
2
49
0
Order By: Relevance
“…The role of in-mixing is prominent when there are large gradients in these tracers between the tropics and the extratropics. The study of Abalos et al (2013) shows that the main contribution to in-mixing originates in the Northern Hemisphere and is related to the ASM, and this in-mixing process takes place in the TTL close to the tropopause. These extratropics to tropics transport events are also considered to be driven by anticyclonic Rossby wave breaking (Homeyer and Bowman, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of in-mixing is prominent when there are large gradients in these tracers between the tropics and the extratropics. The study of Abalos et al (2013) shows that the main contribution to in-mixing originates in the Northern Hemisphere and is related to the ASM, and this in-mixing process takes place in the TTL close to the tropopause. These extratropics to tropics transport events are also considered to be driven by anticyclonic Rossby wave breaking (Homeyer and Bowman, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In various studies, this quasi-isentropic transport from extratropics to the TTL is referred to as an inmixing process (e.g., Konopka et al, 2009). Horizontal inmixing of tracer species has been observed (e.g., Folkins et al, 1999) or modeled (e.g., Konopka et al, 2010), and has been used to explain the seasonal and annual cycle of tracer species (Abalos et al, 2013;Ploeger et al, 2013). The role of in-mixing is prominent when there are large gradients in these tracers between the tropics and the extratropics.…”
Section: Discussionmentioning
confidence: 99%
“…From an Eulerian point of view, changes in the vertical flux must be balanced by horizontal exchange due to mass conservation. From a Lagrangian perspective, the vertical velocity of an air parcel determines the effectiveness of a local in-mixing region, for example by the Asian monsoon anticyclone as described by Ploeger et al (2012); Abalos et al (2013). In the following, we concentrate on tropical upwelling as it is easier to quantify than in-mixing.…”
Section: Tropical Upwellingmentioning
confidence: 99%
“…Its local mixing ratio is considered to result from a stationary state involving production by oxygen (O 2 ) photo-dissociation and a steady influx of O 3 -poor tropospheric air from below (Avallone and Prather, 1996;Waugh et al, 2009;Meul et al, 2014). Meridional mixing from higher latitudes is another factor that contributes to the seasonality in the O 3 mixing ratios (Konopka et al, 2009;Ploeger et al, 2012;Abalos et al, 2013), with the largest impact during boreal summer directly above the tropopause (≈ 380 K/17 km). Several studies have reported a negative trend of O 3 in the tropical LS in the range of −(3-6) % per decade from about 1985 onwards, consistent with the CCM predicted increase of tropical upwelling (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the large ozone annual cycle has been attributed to the annual cycle in the tropical mean upwelling [Randel et al, 2007], and a negative trend deduced from Stratospheric Aerosol and Gas Experiment (SAGE) ozone data has been attributed to an increase in the upwelling bringing more ozone-poor air into the lower stratosphere [Randel and Thompson, 2011]. More recent studies have presented evidence that quasi-horizontal mixing with the extratropics plays an important role, at least for the annual cycle [e.g., Konopka et al, 2009Konopka et al, , 2010Ploeger et al, 2012;Abalos et al, 2012Abalos et al, , 2013aAbalos et al, , 2013b. While the above studies have all used ozone observations to estimate transport rates, they have all focused on variations in the tropic-wide average (of ozone and upwelling).…”
Section: Introductionmentioning
confidence: 99%